Impact of Remittance in Women Education: An Empirical Study - Sapkota, Bhaba Datta; Malakar, Indra Mali (Patan Pragya, 2021)
This study aims at exploring the impact of remittance on women's education while employing descriptive cum cross sectional research design. For this purpose, conveniently Raghuganga Rural Municipality, Ward no. 3, (Mauwaphant area), Myagdi District of Gandaki Province and to well represent the universe, 19 households were randomly selected receiving the remittance. Fieldwork method including in-depth interviews, semi-structured questionnaires, focus group discussion, key informants interview, and case study were the basic tools used in this study for obtaining the primary data which were then analyzed by using simple statistical tools such as tabulation, classification, frequency and percentage. The study argues that remittance raises school enrollment, school completion rate, and private school enrolment and thus improving the educational status of women in general and girls in particular in comparison to the past and have brought the qualitative change in children’s educational status. It concludes that remittance can lift budget constraints, thereby providing children in remittance-receiving households the opportunity to go to school and finally directly benefits the households. Wrapping up, this type of study is pertinent as it would attract public attention in terms of policy that could lead to extensive positive policy initiatives for more detailed discussions and their productive usages for crucial policy concern in Nepal.